Corruption in Latin America - Arellano Gault, David (Routledge, 2020)
"In Corruption in Latin America the reader is presented with an alternative starting point for understanding corruption in this key region. The author asserts that corruption is a stable and rational social and organizational mechanism. Seen through this lens, we can begin to understand why it persists, and how to implement strategies to control corruption effectively. Beginning with an in-depth, nuanced examination of the concept of corruption, the author establishes the theoretical basis for viewing corruption as a social construct. An analysis of the experiences of three countries in the region - Argentina, Brazil, Guatemala and Mexico - provides the reader with concrete data from which they can understand how and why these behaviors are reproduced, validated, and tolerated in everyday settings between governments and citizens, governments and firms, and firms and clients. Once we see corruption as the socially sanctioned norm for getting business done, we can begin to produce and propose effective solutions to reduce corruption in Latin America by designing and implementing instruments that transform this dynamic. This rigorous and original approach will challenge the reader's assumptions about corruption, and will appeal to students of corporate governance, international business, public management, and business ethics"--